Legal Protection for Land Buyers Who Have Not Registered the Transfer of Land Rights After the Seller is Declared Bankrupt by the Commercial Court at the District Court - Rachmawan Mapareppa, Andi; Djunaedi, Djunaedi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. Developers who have been declared bankrupt can cause various legal consequences for the community, one of which is home buyers. Home buyers have made a Sale and Purchase Agreement with the developer. However, if the developer goes bankrupt, the house becomes bankrupt property as long as it is still recorded as a PPJB and the purchase has not been carried out by AJB before the PPAT. In this article, the author wants to examine the legal protection for home buyers if the developer is declared bankrupt. Purposeof this study is to analyze: 1) How is the Legal Force of the Deed of Sale and Purchase Agreement (PPJB) against the Deed of Sale and Purchase (AJB) that has not been made by a notary because the developer is bankrupt 2) How is the Legal Protection for Land Buyers Who Have Not Registered the Transfer of Land Rights After the Seller is Declared Bankrupt by the Commercial Court at the District Court? 3) What are the Settlement Steps that must be taken by the Curator to protect the interests of the Buyer? This type of research is normative legal research. The approach method in this study is a Qualitative approach. The types and sources of data in this study are primary and secondary data obtained through literature studies and documentation. The results of the study are that in filing Other Lawsuits starting from the Registration of Lawsuits that must be filed by an advocate, Lawsuits must be filed with the Chairman of the Commercial Court at the District Court, the trial process is held within a maximum period of 20 days from the date of registration. Keywords: Agreement; Bankruptcy; Law; Protection.